Inclusion of Individuals With Neurodevelopmental Disorders in Norm-Referenced Language Assessments - Loveall, Susan J.; Channell, Marie Moore; Mattie, Laura J.; Barkhimer, Alexandria E. (Frontiers in Psychology, 2022)
Standardized, norm-referenced language assessment tools are used for a variety of purposes, including in education, clinical practice, and research. Unfortunately, norm-referenced language assessment tools can demonstrate floor effects (i.e., a large percentage of individuals scoring at or near the lowest limit of the assessment tool) when used with some groups with neurodevelopmental disorders (NDDs), such as individuals with intellectual disability and neurogenetic syndromes. Without variability at the lower end of these assessment tools, professionals cannot accurately measure language strengths and difficulties within or across individuals. This lack of variability may be tied to poor representation of individuals with NDDs in normative samples. Therefore, the purpose of this study was to identify and examine common standardized, norm-referenced language assessment tools to report the representation of individuals with NDDs in normative samples and the range of standard/index scores provided. A systematic search identified 57 assessment tools that met inclusion criteria. Coding of the assessment manuals identified that most assessment tools included a “disability” or “exceptionality” group in their normative sample. However, the total number of individuals in these groups and the number of individuals with specific NDDs was small. Further, the characteristics of these groups (e.g., demographic information; disability type) were often poorly defined. The floor standard/index scores of most assessment tools were in the 40s or 50s. Only four assessment tools provided a standard score lower than 40. Findings of this study can assist clinicians, educators, and researchers in their selections of norm-referenced assessment tools when working with individuals with NDDs.